Construction of a S-scheme CdS/CuFe2O4 heterojunction with suppressed charge recombination for enhanced visible light-driven photocatalytic activity. (28th February 2023) - Akshhayya, C.; Ansari, Mohammad Omaish; Janani, B.; Subhiksha, V.; Melaibari, Ammar A.; Hasan, P. M. Z.; Asad, Mohammad; Sudheer Khan, S.
Abstract : Coupling p–n semiconductors to form S-scheme interfacial heterojunction to fabricate a suitable nano-photocatalyst for environmental remediation. Abstract : Effective interfacial engineering to fabricate a suitable nano-photocatalyst for environmental remediation is on high demand. A magnetic nanocomposite is a potential candidate for reusability and recovery from treated wastewater. CuFe2 O4 /CdS nanoclusters (NCs) were fabricated using a chemical co-precipitation method. SEM and TEM images of the fabricated NCs revealed coral-like agglomerations and polycrystalline nature of NCs with clear lattice fringes. XPS and EDAX were performed for elemental analysis. The apparent photodegradation rate of dye by NCs is two-fold higher compared to that of pure CdS and CuFe2 O4 . The S-scheme interface retained both strong potential e − /h + for ˙OH and ˙O2 − production under visible light illumination. A 97.71% photocatalytic efficiency was retained after six cycles of reuse. This enhancement in the photocatalytic performance of NCs demonstrates their excellent potential to behave as environmental remediating agents.